The hermeneutics of Torah: Proverbs 2, Deuteronomy, and the composition of Proverbs 1-9 - Schipper, Bernd U. (Ancient Israel and its literature, 2021)
Introduction -- Textual analysis: The instruction of Proverbs 2 -- On the tradition history of Proverbs 2 -- Proverbs in the context of the Book of Proverbs -- The hermeneutics of Torah: Deuteronomy and Proverbs -- Conclusion.